Small-Cell Carcinoma of the Prostate – Challenges of Diagnosis and Treatment: A Next of Kin and Physician Perspective Piece - Trish Abbott; Kenrick Ng; Jenny Nobes; Paula Muehlschlegel (Oncology and Therapy, 2023)
Abstract This article was co-authored by a patient’s relative describing their experiences of receiving a diagnosis and subsequent clinical management of a rare form of prostate cancer, neuroendocrine prostate cancer (NEPC). The difficulty of receiving this diagnosis, particularly as this was terminal with no options for systemic treatment, and experiences throughout this process are detailed. The relative’s questions regarding the care of her partner, NEPC and clinical management are answered. The treating physician’s perspective regarding clinical management is enclosed. Prostate cancer remains one of the most common cancer diagnoses, with small-cell carcinoma (SCC) of the prostate representing 0.5–2% of these. Prostatic SCC frequently develops in patients previously treated for prostate adenocarcinoma, more rarely arising de novo. Diagnosis and management present clinical challenges owing to its rarity, frequently aggressive disease course, lack of specific diagnostic and monitoring biomarkers, and treatment limitations. Current pathophysiological understanding of prostatic SCC, genomics and contemporary and evolving treatment options in addition to current guidelines are discussed. Written principally from the patient’s relatives and physician experience with discussion of current evidence, diagnostic and treatment options, we hope this piece is informative for both patients and healthcare professionals alike.